ENGLISH AND UZBEK LANGUAGES: STRUCTURAL-SEMANTIC FEATURES AND TRANSLATION OF ENERGY SECTOR TERMINOLOGY - Ashiraliyeva Nilufar (Galaxy International Interdisciplinary Research Journal, 2023)
This article explores the structural and semantic features of terms related to the field of energy in English and Uzbek languages, along with their translations. The energy sector is a vital component of global infrastructure, playing a crucial role in powering economies and sustaining modern lifestyles. As the demand for energy continues to rise, effective communication within the sector becomes increasingly important. One significant aspect of this communication is the translation of terms between languages, ensuring that technical jargon is accurately conveyed.